KNOWLEDGE, ATTITUDES, AND PRACTICES REGARDING CHATBOTS AMONG HEALTHCARE PROFESSIONALS IN A TERTIARY CARE HOSPITAL - REGINA ROY; ANIKET; FAZULU RAHIMAN; VIJAYAMATHY (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective: (1) Primary: Determine healthcare professionals’ knowledge, attitudes, and practices (KAP) related to AI Chatbots. (2) Secondary: Assess healthcare professionals’ perspectives on using Chatbots as teaching tools and implementing them in the Competency-Based Medical Education curriculum. Methods: An online questionnaire was distributed to 132 health professionals, including faculty and CRMIs, through Google Forms. Data on artificial intelligence (AI)-related KAP and barriers were collected following IHEC approval. The KAP scores, along with the relationship between categorical variables – such as population type and the use of AI Chatbots – were analyzed using Statistical Package for the Social Sciences software. Results: The study revealed that participants had a moderate level of knowledge about AI Chatbots. Attitudes were mixed, with some skepticism about AI replacing human teachers but also recognition of its benefits. Most participants infrequently used AI Chatbots in their daily activities. Barriers to usage included lack of knowledge, limited access, time constraints, and curriculum gaps. Conclusion: This study underscored the need to enhance medical education with AI topics and address existing barriers. It is crucial to better prepare health professionals for AI integration to leverage AI’s potential for improving patient care and training.